2016
DOI: 10.1371/journal.pone.0158294
|View full text |Cite
|
Sign up to set email alerts
|

Targeted HIV-1 Latency Reversal Using CRISPR/Cas9-Derived Transcriptional Activator Systems

Abstract: CRISPR/Cas9 technology is currently considered the most advanced tool for targeted genome engineering. Its sequence-dependent specificity has been explored for locus-directed transcriptional modulation. Such modulation, in particular transcriptional activation, has been proposed as key approach to overcome silencing of dormant HIV provirus in latently infected cellular reservoirs. Currently available agents for provirus activation, so-called latency reversing agents (LRAs), act indirectly through cellular path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 49 publications
4
67
0
10
Order By: Relevance
“…These strategies can be a useful alternative to transgene overexpression or antisense-mediated gene repression. In fact, several studies have already demonstrated its applicability in the validation of gene functionality (Gilbert et al, 2014; Chavez et al, 2016; Radzisheuskaya et al, 2016), interrogation of promoter and enhancer regions (Kearns et al, 2015; Zalatan et al, 2015; Himeda et al, 2016; Klann et al, 2017), induction of direct cell fate conversion (Chakraborty et al, 2014; Balboa et al, 2015; Black et al, 2016), reprogramming to pluripotency (Balboa et al, 2015; Xiong et al, 2016), genome-scale transcriptional modifications (Gilbert et al, 2014; Konermann et al, 2015) and proof of concept therapeutic approaches against various diseases (Bialek et al, 2016; Braun et al, 2016; Garcia-Bloj et al, 2016). …”
Section: Cas9-mediated Chromatin Modificationsmentioning
confidence: 99%
“…These strategies can be a useful alternative to transgene overexpression or antisense-mediated gene repression. In fact, several studies have already demonstrated its applicability in the validation of gene functionality (Gilbert et al, 2014; Chavez et al, 2016; Radzisheuskaya et al, 2016), interrogation of promoter and enhancer regions (Kearns et al, 2015; Zalatan et al, 2015; Himeda et al, 2016; Klann et al, 2017), induction of direct cell fate conversion (Chakraborty et al, 2014; Balboa et al, 2015; Black et al, 2016), reprogramming to pluripotency (Balboa et al, 2015; Xiong et al, 2016), genome-scale transcriptional modifications (Gilbert et al, 2014; Konermann et al, 2015) and proof of concept therapeutic approaches against various diseases (Bialek et al, 2016; Braun et al, 2016; Garcia-Bloj et al, 2016). …”
Section: Cas9-mediated Chromatin Modificationsmentioning
confidence: 99%
“…A novel means to activate HIV-1 is to use catalytically-deficient Cas9-synergistic activation mediator (dCas9-SAM) technology as a method to selectively and potently reactivate latent viral reservoirs. It has been possible to screen and identify gRNAs within the HIV-1 LTR that induce robust reactivation of provirus [79,80], which induced cellular suicide via toxic buildup of viral proteins suggesting that this might serve as a novel HIV-latency-reversing therapeutic tool for eliminating HIV-1 latent reservoirs.…”
Section: Crispr/cas9 For Novel Gene Editing Aids Therapiesmentioning
confidence: 99%
“…However, since extended expression of CRISPR/Cas9 in the cells is necessary with this tactic, off-target effects may become a problem as explained above. A related approach has been to use a catalytically-deficient Cas9-synergistic activation mediator (dCas9-SAM) as a means to activate the HIV-1 provirus similar to the “shock and kill” approach only with a novel and more specific viral latency-reversing tool (Zhang et al, 2015a; Bialek et al, 2016). …”
Section: Recent Applications Of Crisprmentioning
confidence: 99%
“…In addition, catalytically inactive Cas9 (dCas9) can be fused to other proteins and used together with gRNA to exert sequence-specific targeted effects such as gene activation or gene silencing. For example, dCas9-SAM can be used as a means to activate HIV-1 provirus as discussed above (Zhang et al, 2015a; Bialek et al, 2016). dCas9 derivatives can also be used to execute target-specific epigenetic changes such as DNA methylation and histone acetylation (Cano-Rodriguez and Rots, 2016).…”
Section: Recent Applications Of Crisprmentioning
confidence: 99%